Comparative evaluation of fluoride release and recharge of pre-reacted glass ionomer composite and nano-ionomeric glass ionomer with daily fluoride exposure: An in vitro study - Jayanthi Mungara; John Philip; Elizabeth Joseph; Sakthivel Rajendran; Arun Elangovan; Girija Selvaraju (Wolters Kluwer Medknow Publications, 2013)
Aim: This in vitro study was designed to investigate the effects of daily fluoride exposures on fluoride release and recharge by prereacted glass ionomer (PRG) composite and nano-ionomeric glass ionomer. Materials and Methods: Seventy-two specimens (36 of each material) were prepared and by placing the restorative materials into Teflon mold. Each specimen was subjected to one of three daily treatments (n = 12): (1) No fluoride treatment (control); (2) application of a fluoride dentifrice (1,000 ppm) once daily; and (3) the same regimen as (2), plus immersion in a 0.05% sodium fluoride (NaF) mouth rinse (225 ppm) immediately following the dentifrice application. Specimens were suspended in a storage vial containing 10 ml demineralizing solution for 6 h and transferred to a new test tube containing 10 ml remineralizing solution for 18 h. Fluoride treatments of the specimens were completed every day prior to their immersion in the demineralizing solution. Media solutions were buffered with equal volumes of total ionic strength adjustment buffer (TISAB) II; fluoride levels were measured using a digital ion analyzer and fluoride electrode throughout the 21 day duration of the experiment. Results: Nano-ionomeric glass ionomer showed a better amount of fluoride release than PRG composite irrespective of the fluoride treatment supplementation (P < 0.01). Additional fluoride supplementation improved fluoride release and recharge ability for both the materials when compared to their respective control groups. The fluoride recharge for both materials did not show any sustained pattern of release. Conclusion: Nano-ionomeric glass ionomer demonstrated a greater ability to release and recharge compared with that of PRG composite.